Systematic Review and Development of Responsible Leadership Scale - Siddiqui, Sulaman Hafeez; Ijaz, Ali; Javeria, Aisha; Naz, Muqaddas (Pakistan Journal of Humanities and Social Sciences, 2023)
The purpose of this paper is to develop a universally accepted measurement scale of Responsible Leadership (RL) based on the triple bottom approach (3BL) which covers environmental, economic, and social aspects at the same time. Systematic literature review of RL conducted along with in-depth interviews conducted with experts of industry and academia. Based on in-depth interviews, a content validity ratio analysis was conducted to examine the content validity of the questionnaire. Explanatory factor analysis using SPSS version 21 and confirmatory factor analysis using AMOS were conducted to test the reliability and validity of the questionnaire. A sample of 329 respondents working in the banking sector was taken for data analysis. Eigenvalues result confirms the triple bottom approach that RL is a three-dimensional construct and measured by economic, social and environmental aspects. These three dimensions explain 66.83% of the total variance explained. Respondents’ demographic shows that the male section is dominant in the banking sector as 83.6% of respondents were male and 16.4% were female. The economic dimension consists of eight items that have a Cronbach alpha value of 0.97, the social dimension has eight items that have a Cronbach alpha value of 0.90, and the environmental dimension consists of nine items that have a Cronbach value of 0.92. Initially, CFA was conducted with 25 items, then implemented modification indices and the final CFA was conducted with 23 items and all indicators of model fitness were found up to standard. The outcome of the present study is in form of a measurement scale based on the triple bottom approach which covers economic, social and environmental aspects of leadership. It is hoped that this scale will be potentially helpful for future researchers to measure RL and check the relationship with other potential variables. This systematic literature review and scale will allow future researchers to explore and conduct empirical studies in banking and other sectors. This paper responded to various calls regarding the universally accepted measurement scale of RL by developing the RL measurement scale.